Pembelajaran bahasa Arab berbasis kurikulum K13 di Madrasah Aliyah Al Khoirot Malang - Nidhom, Moch (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to describe the methods, factors and problems in Arabic language learning at Madrasah Aliyah. This research uses qualitative research methods of case study type. With data collection techniques interviews with teachers and some students of Madrasah Aliyah Al Khoirot Malang in the academic year 2022/2023. The results of this study describe that 1. The methods used in Arabic language learning based on the 2013 curriculum and skills in Arabic teaching and learning activities or can be called maharah, 2. inhibiting and supporting factors that affect Arabic teaching and learning activities in Madrasah Aliyah, one of the inhibiting factors is monotonous learning methods and teachers who cannot liven up the atmosphere of the learning class, as well as problems in Arabic language learning in Madrasah Aliyah, namely the different backgrounds of students so that they are also different in terms of understanding and ability in Arabic. While the supporting factors in Arabic language learning are teachers looking for broader and more effective learning media so that 2013 curriculum learning can run in a structured manner.